THE ROLE OF ENGLISH EDUCATION AS THE SOLUTION OF THE SOCIAL WELFARE PROBLEM IN INDONESIA - Anisah Setyaningrum (P3M STAIN Kudus, 2016)
The problem of social welfare becomes the theme which has been often to be discussed. This paper aims to describe the role of English Education as the solution of society’s welfare problem in Indonesia. English as an international language has become a compulsory subject in every level of education since last two decades. There are many advantages that can be gained by mastering English well, one of them is able to improve someone’s welfare level. One of the roles of English in increasing the Indonesian society’s welfare is English can be a potential provision in conducting entrepreneurship. In the other hand, it will increase their income. Besides, by having a good English mastery can facilitate them in gaining a better job.